EFEKTIVITAS INSTAGRAM SEBAGAI MEDIA KOMUNIKASI PEMASARAN AGROWISATA WIWANDA AGROW, DESA PANCASARI, KABUPATEN BULELENG - Laras Putri Damayanti (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Marketing communication is a tool used to inform, persuade, and remind consumers about products and brands. Social media plays a key role in this, as its user base continues to grow. It enables interactive dialogue through web-based platforms. This study aims to analyze the characteristics of Instagram users and the effectiveness of Instagram as a marketing communication medium for Wiwanda Agrow agrotourism using quantitative descriptive methods. Data were collected via a questionnaire distributed through Google Forms with 44 respondents, selected using simple random sampling. The results show that @wiwandaagrow users are mostly women aged 17–30 with a Diploma or Bachelor’s degree. As a visual marketing tool, Instagram content falls into the highly attractive category. Based on the AISAS model, Instagram proves effective in attracting interest, providing information, and encouraging visits. Instagram helps introduce agrotourism, convey key messages, and build engagement. Therefore, Wiwanda Agrow is advised to consistently share content related to tourism activities to enhance visitor interest